THE POETRY OF THE INDIAN TRIBALS - Thuruthumalil, Abraham (Journal of Dharma, 1992)
The primitive poem or song is part of a complex of communal activity which includes singing, dancing, religious activity and celebration on social occasion. The songs, the dances and the relevant festivities are intimately and jntegraly related. For celebrating each important religious festival or socio religious ceremony the tribals have got an appropriate set of songs and dances. It is necessary to view these poem-songs as part of such a communal activity which is not true of modern poetry. In other words tribal poems are nothing but the 'unwritten record' of tribal fife. They are also highly musical. Most of the songs circulate by the process of oral transmission and their roots lie buried deep in the group life of the tribes. Most of the songs have come down from generations and the performers learn them from their elders. Thus the continuity of the old generation is well maintained.